A GTN-like Model for Plastic Porous Materials - Siad, L.; Gangloff, S. C. (Engineering, Technology & Applied Science Research, 2014)
An extended version of the well-known Gurson-Tvergaard-Needleman (GTN) isotropic hardening model is presented in this paper. The yield function of the proposed constitutive model possesses the distinctiveness to explicitly depend upon the third stress invariant. The presented constitutive model is used to analyze the necking of a round tensile bar. As long as softening initiation of specimen is not reached, the obtained numerical results highlight similarities and good agreement with those provided by the use of the GTN model. However, discrepancy shows up as soon as specimen failure starts.